Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 527 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Erythrura gouldiae (Gould, 1844)", "HasGeospatialIssue is false", "Geometry POLYGON((126 -19,126 -16,130 -16,130 -19,126 -19))" ] } The dataset includes 527 records from 9 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000815-150216165555722/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences